ELECTORAL MALPRACTICE DALAM PUNGTURA (PEMUNGUTAN, PENGHITUNGAN, DAN REKAP) PILKADA BUPATI MOJOKERTO 2020 - Saifulloh, Ahmad Iklil (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Abstract Based on Mojokerto Regency Election in December 2020, the total number of the Permanent Voters List (DPT) was 823,014 votes with a total specification of 621,096 valid ballots and 27,327 invalid votes. So the total valid and invalid votes amounted to 648,423 votes with the details of pair number 1, Ikfina Fatmawati and Muhammad Albarra getting a total of 405,157 votes. While the pair number 2, Yoko Priyono and Choirun Nisa, received a total of 95,481 votes, and the pair number 3 with the names Pungkasiadi and Titik Malalu received a total of 120,458 votes. and the focus of this research is 4% of invalid ballots which in the Mojokerto Regent's regional head election held in December which is having various, patterns and forms of invalid votes. This research was using the Normative Qualitative method with Han Kelsen's Pure Legal Positivism approach to legal materials and primary and secondary regulations. The source of data in the form of premiere is direct data from the Mojokerto KPU. Secondary data comes from reference books, journals, archives, documents, reports which are corroborated by expert validation regarding the findings. The results obtained are summarized in three general aspects; first is related to ignorance due to limited socialization during the pandemic regarding the qualifications of valid and invalid ballots, second is related to technical errors or electoral malpractice factors in the form of 4 patterns or varieties of invalid ballots in the form of; 1. there is a check mark on both pairs of candidates; 2. The ballot mark is on the outside of the column for the candidate pair; 3. ballot marks on the column of candidate pairs and outside the column of candidate pairs, and 4. damaged/torn ballots. The last one related to the 5 criteria of Form C6 whis is being returned, however in the Mojokerto Regency Pilkada only 4 factors were found that affected Form C6 notifications that were not delivered to voters; 1. Past away, 2. Changed address, 3. Could not be found, 4. Others. Key word: PUNGTURA, Invalid Ballots, Electoral Malpractice Abstrak Dalam penghitungan suara Pilkada Kabupaten Mojokerto pada bulan Desember 2020, Jumlah total keseluruhan dari Daftar Pemilih Tetap (DPT) adalah 823.014 suara dengan spesifikasi total surat suara sah sebanyak 621.096 dan tidak sah sebanyak 27.327 suara. Jadi total suara sah dan tidak sah berjumlah 648.423 suara dengan perincian pasangan nomer urut 1, Ikfina Fatmawati dan Muhammad Albarra mendapatkan total 405.157 suara. Sedangkan pasangan nomor urut 2, Yoko Priyono dan Choirun Nisa memperoleh toal suara sebanyak 95.481, dan pasangan nomor urut 3 dengan nama Pungkasiadi dan Titik Masudah memperoleh total suara sebanyak 120.458. dan fokus penelitian ini adalah 4% surat suara yang tidak sah yang mana dalam Pemilihan kepala daerah Bupati Mojokerto yang diadakan pada bulan Desember terdapat ragam, pola dan bentuk suara tidak sah dengan metode Qualitatif Normatif dengan pendekatan Legal Positivistik Hukum Murni Han Kelsen terhadap bahan hukum dan peraturan premier dan sekunder. Sumber data dalam bentuk premier berupa data langsung dari KPU Mojokerto. Data sekunder berasal dari buku referensi, Jurnal, Arsip, Dokumen, Laporan yang dikuatkan oleh validasi ahli terkait temuan. Hasil yang diperoleh terangkum dalam tiga aspek general; yang pertama terkait ketidak tahuan dikarenakan keterbatasan sosialisasi pada masa pandemi terkait kualifikasi surat suara yang sah dan tidak sah, yang kedua terkait foktor kesalahan teknis atau electoral malpractice berupa 4 pola atau ragam surat suara tidak sah berupa; 1. terdapat tanda coblos pada kedua pasangan calon; 2. tanda coblos berada pada luar kolom pasangan calon; 3. tanda coblos pada kolom pasangan calon dan di luar kolom pasangan calon, dan 4. surat suara yang rusak/robek. Yang terakhir terkait 5 kriteria Form C6 dikembalikan, akan tetapi di Pilkada Kabupaten Mojokerto hanya di temukan 4 Faktor yang mempengaruhi Form C6 Pemberitahuan yang tidak tersampaikan ke pemilih; 1. Meninggal Dunia, 2. Pindah Alamat, 3.Tidak Dapat Ditemui, 4.Lain-Lain. Kata Kunci: PUNGTURA, Surat Suara Tidak Sah, Electoral Malpractice,